Food Insecurity Resilience Capacity of Rural Households in the Face of Induced-Weather Extremities in Bauchi State of Nigeria - Mohammed Sadiq; Muhammad Ahmad; Mahmood Bala; Invinder Singh (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
It is no longer a chasm that human existence is being threatened by induced-weather vagaries. Given the dynamic nature of the weather vagaries, if tacit actions are not taken on continuum basis, soonest, human race will go into extinction because of the steep devastating push effect of climate change. It is in lieu of the foregoing, that the researchers conceptualized a study that assessed rural households’ food insecurity resilience capacity in Nigeria’s Bauchi state using a resilience index measurement analysis (RIMA II), a novel methodological approach developed by FAO for studying such scenario, as literature review showed no evidence of its application in the study area. Adopting a multi-stage random sampling technique, a total of 322 households were randomly sampled from a sampling frame obtained by a reconnaissance survey. Using a well-structured questionnaire complemented with interview schedule, rural households’ survey data were collected in the year 2022. Besides, the collected data were analyzed using both descriptive and inferential statistics. Empirically, it was established that the study area is challenged with food insecurity that owes majorly to poor food utilization and stability. Besides, poor food insecurity resilience capacity majorly due to vulnerable adaptive capacity was unmasked as the push effect behind food insecurity bane in the study area. However, evidence showed that food insecurity resilience capacity has a lasting effect on general well-being of rural households while households’ hunger resilience capacity has a transitory effect as it can only contain food crises on the short-term basis. Nevertheless, income and consumption smoothening were the commonest short-term food coping strategies adopted in the study area. To achieve the sustainable development goals of zero hunger by 2030, it becomes imperative on policymakers to sensitize rural households on the need to adopt safe and eco-friendly improved indigenous food technologies so as to address the poor states of food utilization and stability affecting food security of the study area.